Development of calcium oxide-based catalyst derived from waste shell for biodiesel production from Nannochloropsis oculata oil and palm fatty acid distillate - Osman, Nur Syazwani (2017)
Excessive use of petroleum in transportation and industry, leads to acceleration of greenhouse gas emissions and the depletion of petroleum reserves worldwide. In order to reduce the environmental issues, research on alternative fuel which can replace the dependency on non-renewable petroleum based fuel is crucial. In this research, calcium oxide, (CaO) derived from three different waste shells (Angel Wing, Etok and Green Mussel) were used as catalyst for transesterification of microalgae oil, Nannochloropsis oculata. The microalgae oil was extracted after cultivating and harvesting for several weeks. Calcined angel wing shell (CAWS) at 900 ̊C shows highest FAME yield (84.11%) at oil:methanol molar ratio 1:150 and catalyst loading of 9 wt.% in 1 h reaction and can be reused for more than three times. In order to reduce cost production of biodiesel, low cost feedstock such as palm fatty acid distillate (PFAD) was also used by using sulfated CAWS catalysts. CAWS precursor was sulfated using different sources of SO42- ions with varied concentration at ambient temperature. All the catalysts were characterized by using thermogravimetric analysis (TGA), X-ray diffraction spectroscopy (XRD), Fourier transforms infrared spectroscopy (FT-IR), temperature programmed desorption of carbon dioxide (TPD-CO2), temperature programmed desorption of ammonia (TPD-NH3), BET surface area and variable pressure scanning electron microscope (VPSEM). In addition, esterification reaction of PFAD by using a conventional reflux with the presence of CAWS(7)-H2SO4 catalyst shows 98% of FAME yield at 1:15 PFAD/ methanol molar ratio, 5 wt.% of catalyst loading at 80 ̊C for 3 h reaction. The catalyst also can be reused at least two times with 98% of FAME yield without further treatment. The reused or spent catalyst was analyzed to determine the deactivation mechanism of the reused catalyst. Besides, esterification of PFAD in supercritical methanol reaction produced 97.9% of FAME yield with PFAD/methanol molar ratio 1:6, 2 wt.% of catalyst loading at 290 ̊C for 15 minutes. The CAWS-(7)H2SO4 catalyst can be reused up to seven cycles with FAME yield more than 80 %.The fuel properties were also investigated by using ASTM and European standard method and it was found that the PFAD methyl ester was met the biodiesel quality standard and has almost similar property with petrol fuel. As a conclusion, both CAWS and CAWS(7)-H2SO4 show outstanding performance as low cost heterogeneous basic and acid catalyst, respectively for biodiesel production from either low or high FFA feedstocks.